- PENGARUH UKURAN PERUSAHAAN, KONSENTRASI KEPEMILIKAN, DAN KOMISARIS INDEPENDEN TERHADAP PENGUNGKAPAN INTELLECTUAL CAPITAL: (Studi Pada Perusahaan LQ45 Yang Terdaftar di Bursa Efek Indonesia Periode 2018-2021) - Setiawan, Faysa Adityar; Suzan, Leny (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
Contracts between management and employees are now governed by a new type of communication known as disclosure intellectual capital. This allows managers to develop strategies to meet the demands of stakeholders such as investors and to convince them of the benefits or advantages of company policies. Intellectual capital disclosure is information the company provides regarding managing and utilizing owned intellectual capital. Intellectual capital disclosure needs to be done because it can reduce information asymmetry between management and stakeholders. This study aims to determine whether company size, the concentration of ownership, and independent commissioners have an effect on intellectual capital disclosure in LQ45 companies listed on the Indonesia Stock Exchange for the 2018-2021 period. The data analysis technique in this study used a panel data regression model. The research results show that company size, ownership concentration, and independent commissioners simultaneously affect intellectual capital disclosure. While partially, ownership concentration affects intellectual capital disclosure. Company size and independent commissioners do not affect intellectual capital disclosure.